Attitudes of psychiatric nurses toward restraint interventions in Italian mental health care: Implications for clinical practice - Vitale, Elsa; Lupo, Roberto; Farì, Martina; Fanton, Marta; Lezzi, Alessia; Calabrò, Antonino; Ercolani, Maurizio; Carvello, Maicol; Artioli, Giovanna; Conte, Luana; De Nunzio, Giorgio (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: To analyze psychiatric nursing attitudes and believes on restraint nursing approachesMethods: An observational and cross sectional study was carried out on nurses employed in mental health facilities trough a questionnaire administered on-line. The questionnaire was created specially for the purpose of the study and contained 5 main sections: i. socio-demographic data, attituded towards physical restraint, and the de-escalation attitude in the psychiatric nurses interviewed. For each item a response between “always”, “sometimes”, and “never” was proposed. Descriptive and inferential statistics were assessed.Results: 268 psychiatric nurses were enrolled in this study. The data reported that most of the participants had over six years of work experience in mental health and 80% received training on physical restraint during their nursing degree, mostly in the post-base update. Conflicting opinions with respect to physical constraints as safe tools to prevent skin lesions, and to the risks associated with this practice, were revealed.Conclusions: Implementing educational programs for healthcare personnel seemed imperative, focusing on equipping them with strategies to minimize the use of restraint and to effectively adapt to the anticipated transformations in contemporary psychiatry.